Perancangan Tata Letak Fasilitas dan Tata Letak Produk di Gudang Marketplace Perusahaan Bloods Industries - Yohanes Arifin; Anggoro Prasetyo Utomo (Jurnal Serambi Engineering, 2024)
Bloods Industries is a company engaged in the production and distribution of ready-made clothing in Bandung. The clothing is distributed from warehouses located in the city. These warehouses include an offline store warehouse and a marketplace warehouse. Observations of the marketplace warehouse revealed a lack of order in product placement, with many items lying on the floor. This study aims to design the layout of the facilities and product placement in the marketplace warehouse to minimise the distance travelled to place and retrieve products. The design process uses the Activity Relationship Chart (ARC) method to understand the relationships between facilities, the Total Closeness Rating (TCR) method to identify priority facilities, the ABC classification method with a popularity principle to determine frequently rotated products, and the Dedicated Storage, Class Based Storage method to place products in fixed positions due to the availability of many facilities. The redesign results in a new layout for both facilities and product placement, significantly reducing travel distances. The initial travel distance before the redesign was 441.9 m over an area of 13.9 m x 7.1 m. And the new travel distance is 176.83m in an area of 10.2m x 12.1m.